2020
DOI: 10.1017/mor.2020.46
|View full text |Cite
|
Sign up to set email alerts
|

Renaissance of Resilience: A Buzzword or a New Ideal?

Abstract: The COVID-19 pandemic, an unprecedented public health crisis in the 21 st century, demonstrates how risks are unequally distributed among different socioeconomic groups, how bureaucratic systems can be ineffectively adapting to the fast-paced changing dynamics, and how multi-level governance frameworks may lack coordination between national and regional sectors. The pandemic does not cause the unjust prerogatives to quarantine, testing kits, and even potential vaccines. The injustice, ineffectiveness, and a la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…People using positive coping strategies, such as planning, acceptance and reframing, have higher levels of resilience. This is in line with a study carried out on health care professionals, which showed that having positive attitudes in the workplace is associated with low levels of distress [57], greater psychological wellbeing, and better quality of life [81,82].…”
Section: Discussionsupporting
confidence: 90%
“…People using positive coping strategies, such as planning, acceptance and reframing, have higher levels of resilience. This is in line with a study carried out on health care professionals, which showed that having positive attitudes in the workplace is associated with low levels of distress [57], greater psychological wellbeing, and better quality of life [81,82].…”
Section: Discussionsupporting
confidence: 90%
“…The COVID-19 pandemic has created an urgent crisis exposing several organizational disadvantages, and testing their governance mechanism. In this pandemic, when uncertainty becomes the norm, researchers, decision makers and policymakers from various fields have widely used the notion of resilience (Cai, 2020). The word “resilience” is derived from the Latin resilire , which means to jump back or recoil, and the concept of resilience has been adopted by many disciplines, such as engineering, biology, psychology and ecology (Giustiniano et al , 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The outbreak of COVID-19 soon put the airlines in a very critical situation. Since the start of lockdowns as a consequence of the pandemic, many scholars and practitioners have focused on discussing and recommending the principles of organizational resilience (Cai, 2020). The core of the concept and practice of the resilient organization is that organizations should cope with crises effectively through proactive plans and the ability to bounce back smoothly in recovery (Giustiniano et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Emergency management systems become sorely tested (Cai & Ye, 2020). Do we have a new buzzword for uncertain times (Cai, 2020) or something to learn from that will help in coping with future crises or understanding the renaissance of resilience? Some themes rise above others.…”
mentioning
confidence: 99%